Vitamin E for prevention of oxaliplatin-induced peripheral neuropathy: a pilot randomized clinical trial - Afonseca, Samuel Oliveira de; Cruz, Felipe Melo; Cubero, Daniel de Iracema Gomes; Lera, Andrea Thaumaturgo; Schindler, Fernanda; Okawara, Marcia; Souza, Luiz Fernando de; Rodrigues, Nataly Pimentel; Giglio, Auro del (São Paulo Medical Journal, 2013)
CONTEXT AND OBJECTIVE: Oxaliplatin is one of the chemotherapy regimens most used for treating colorectal cancer. One of the main limitations to its use is induction of peripheral neuropathy. Previous studies have shown that vitamin E can reduce the incidence of peripheral neuropathy by 50%. This study aimed to assess the effectiveness of vitamin E for prevention of oxaliplatin-induced peripheral neuropathy. DESIGN AND SETTING: Prospective, phase II, randomized pilot study developed at a university hospital in the Greater ABC region. METHODS: Patients were randomized five days before starting oxaliplatin treatment, to receive either vitamin E or placebo until the end of the chemotherapy regimen. The outcome was evaluated using the Common Terminology Criteria for Adverse Events (CTCAE), version 3, and specific gradation scales for oxaliplatin-induced peripheral neuropathy. Patients with colorectal and gastric cancer who had been scheduled to receive oxaliplatin-based chemotherapy were included. Both groups received calcium and magnesium supplementation before and after oxaliplatin infusions. RESULTS: Eighteen patients were randomized to the vitamin E group and 16 to the placebo group. Cumulative incidence of 83% with peripheral neuropathy grades 1/2 was observed in the vitamin E group, versus 68% in the placebo group (P = 0.45). A trend towards more diarrhea was observed among patients who received vitamin E (55.6% vs. 18.8%; P = 0.06). There were no other significant differences in toxicity between the groups. CONCLUSIONS: No significant decrease in the incidence of acute oxaliplatin-induced peripheral neuropathy was demonstrated through vitamin E use. CLINICAL TRIAL REGISTRATION: NCT01523574.